Pengaruh Instagram Advertising (Ads) Terhadap Minat Beli Tamu di The Westin Resort Nusa Dua, Bali - Maharani, Ni Wayan Vivian (Program Studi Administrasi Perhotelan, 2025)
Nowadays, the enhancement of social media is increasingly needed by humans in their daily lives, one of which is in terms of getting information about something unlimitedly, which makes social media widely used as a marketing medium. In this research, the author uses Instagram Advertising (Ads) as an example of a social media feature that is popularly used to market products or services. This study aims to determine how much the influence of Instagram Ads views have on guest purchase intention at The Westin Resort Nusa Dua, Bali. The population of this research are worldwide active Instagram users, then the sample is narrowed by determining a representative number of 100 people using the unknown populations method and purposive sampling technique requiring the sample are active Instagram users and has seen Instagram Advertising (Ads) of @westinbali. Respondent data was collected by distributing questionnaires and then processed with SPSS version 29. Data analysis in this study uses simple linear regression test, partial correlation coefficient t test, and determination coefficient test. The result of this research showed that Instagram Advertising (Ads) variable (X) has a positive and significant influence on Customer Purchase Intention (Y) at The Westin Resort Nusa Dua, Bali.